APPLYING UNIVERSAL DESIGN FOR LEARNING (UDL) PRINCIPLES TO A HYBRID UNIVERSITY COURSE TO ENHANCE ACCESSIBILITY FOR ALL STUDENTS - Moana Siaosi; Lepa Palu; Tili Latu (Journal Neosantara Hybrid Learning, 2025)
The rapid expansion of hybrid learning models in higher education has underscored the need for more inclusive instructional designs that accommodate diverse learner profiles. Many university students encounter barriers in digital and physical learning environments due to differences in abilities, learning preferences, and access to technology. This study applies the Universal Design for Learning (UDL) framework to a hybrid university course to evaluate its effectiveness in enhancing accessibility and engagement for all students. The research aims to determine how UDL principles multiple means of representation, engagement, and expression can be systematically integrated into hybrid course design to promote equitable learning opportunities. A mixed-methods design was employed, combining pre- and post-intervention surveys with focus group interviews. The participants included 60 undergraduate students from a teacher education program. Quantitative data were analyzed using paired-sample t-tests to assess changes in students’ perceived accessibility and satisfaction, while qualitative data were examined through thematic analysis. Results indicated a significant increase in students’ accessibility perception, digital engagement, and self-efficacy after the UDL-based redesign. Students reported that flexible content formats, interactive online modules, and multiple assessment options improved their learning experience and reduced participation barriers. The study concludes that integrating UDL principles in hybrid course design effectively enhances inclusivity, promotes active engagement, and supports diverse learning needs. It recommends that universities adopt UDL-based instructional frameworks to ensure equitable access in hybrid and digital education environments.